Category Shift of Noun Phrases Found in the Translation of Romeo and Juliet Novel - Alfa Christin Abidondifu; I Gusti Agung Sri Rwa Jayantini; Ni Wayan Suastini (University of Darussalam Gontor, 2021)
The concern of this study is the translation shift especially the noun phrase category shift. The aims is to identify and clasify the kinds of category shift Indonesian translation Romeo and Juliet novel by William Shakespeare. The data were taken from 2 novel which is the English version and the translation version or Indonesian that has same tittle, Romeo and Juliet. The data were collected using the observation method, which was realized by reading the novel, identifying the category shift, underlining the noun phrase of category shift, and finding the meaning of the words. The data were analyzed by applying the qualitative and descriptive methods. The main theory applied in this study is the theory of translation shift proposed by Catford (1965) and translation process proposed by Larson (1998) which was used to analyze the study aims. The results showed that all of the category shift that proposed by Catford is found in the translation novel. The structure shift occurred in the highest frequency, with consist of 45 or 45% out of the total 100 cases it is because of the different structure grammatical of the source language (English) and target language (Indonesian). And the second most occurrence is unit shift which consists of 25 cases or about 25%. The third is intra-system shift which consists of 20 or 20% and the lowest is class shift which consists of 10 cases or 10% out of the total 100 cases.